(فعالية الطريقة الجزئية لترقية مهارة القراءة (دراسة تجريبية: THE EFFEVTIVENESSOF PARTIAL METHOD TO IMPROVE READING SKILL (AN EXPERIMENTAL STUDY) - Irmasani Daulay (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: This study aims to determine the effectiveness of the Synthesis Method to Improve Students' Reading Ability in MAN 1 Pekanbaru. This study is an experimental research, which is a research method used to look for the effect of certain treatments on others under controlled conditions. Using the experimental design of the Control Group Pretest-Posttest. Based on observations obtained 92% means "Very Good" from the level of 81-100%. And the test results from the analysis of the data obtained, it can be concluded that the Synthesis Method for Improving Students' Reading Ability in MAN 1 Pekanbaru based on the calculated results using the formula namely; the value of To = 4 is greater than Tt at the significance level of 1% = 2.56 and the significance level of 5% = 2.00. this means that Ho is rejected and Ha is accepted. In other words, the Synthesis Method is effective for Improving Students' Reading Ability in MAN 1 Pekanbaru. الكلمات الأساسية : فعالية، الطريقة التركيبية (الجزئية)، مهارة القراءة